2012
DOI: 10.4103/0253-7613.103278
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of anti-inflammatory effect of anti-platelet agent-clopidogrel in experimentally induced inflammatory bowel disease

Abstract: Aim:To evaluate the anti-inflammatory effect of antiplatelet agent, clopidogrel, in experimentally induced inflammatory bowel disease (IBD).Materials and Methods:TNBS induced Crohn's disease model and oxazolone induced ulcerative colitis model were used to evaluate the role of clopidogrel in IBD. Spargue Dawley female and Wistar male rats were used respectively. The colitis was induced by a single intra-colonic application of TNBS (0.25 ml, 120 mg/ml in 50% ethanol) and oxazolone (450 μl 5% oxazolone in 50% et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Statin use was associated with a significantly decreased risk of IBD (OR: 0.68, 95%CI: 0.64-0.72), CD (OR: 0.64, 95%CI: 0.59-0.71), and UC (OR: 0.70, 95%CI: 0.65-0.76)[ 43 ]. Two studies developed animal models of IBD by chemically inducing CD and UC and showed that captopril was implicated in reducing transforming growth factor-beta1 expression and colitis-associated fibrosis[ 44 , 58 ]. Clopidogrel also reduced disease activity index and colonic mucosal damage index in mice – thus providing an additional link between treatment of IBD and ASCVD[ 58 ].…”
Section: Ascvd Risk Modification From Anti-inflammatory Medicationsmentioning
confidence: 99%
“…Statin use was associated with a significantly decreased risk of IBD (OR: 0.68, 95%CI: 0.64-0.72), CD (OR: 0.64, 95%CI: 0.59-0.71), and UC (OR: 0.70, 95%CI: 0.65-0.76)[ 43 ]. Two studies developed animal models of IBD by chemically inducing CD and UC and showed that captopril was implicated in reducing transforming growth factor-beta1 expression and colitis-associated fibrosis[ 44 , 58 ]. Clopidogrel also reduced disease activity index and colonic mucosal damage index in mice – thus providing an additional link between treatment of IBD and ASCVD[ 58 ].…”
Section: Ascvd Risk Modification From Anti-inflammatory Medicationsmentioning
confidence: 99%
“…Nonetheless, blockade of GPIIb/IIIa had no effect on platelet adhesion in an experimental model of colitis [82]. In contrast to RA, pharmacological blockade of P2Y 12 receptor by clopidogrel or treatment with acetylsalicylic acid reveals an attenuated disease course in models of IBD [98,99]. …”
Section: Rheumatoid Arthritismentioning
confidence: 99%
“…Earlier research indicated that clopidogrel enhanced the inhibition of platelet activation, platelet-leukocyte interaction, and P-selectin expression on CD40 lymphocytes through P2Y12 receptor inhibition, which might contribute to the resolution of IBD symptoms. 48 …”
Section: Discussionmentioning
confidence: 99%